2012
DOI: 10.1113/jphysiol.2012.241141
|View full text |Cite
|
Sign up to set email alerts
|

Adverse cardiac remodelling in spontaneously hypertensive rats: acceleration by high aerobic exercise intensity

Abstract: Key points• Physical exercise is recommended as first line therapy for hypertensive patients. However, studies investigating long-term effects of high intensity exercise on the progression of hypertensive heart disease have revealed conflicting results.• We show that high intensity aerobic exercise accelerates hypertensive heart disease and improves fibrosis.• Surprisingly, high intensity aerobic exercise in the presence of an angiotensin converting enzyme inhibitor not only attenuated training induced mal-ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 38 publications
4
46
0
Order By: Relevance
“…Some reports even suggest that exercise training can reduce the development of �brosis in established pathologic hypertrophy [61]. However, a very recent paper has shown that high levels of wheel running velocity in SHR rats can induce a pro�brotic phenotype and is positively correlated with LV mRNA of TGF-1, collagen III, and biglycan, whereas wheel running velocity was negatively correlated with SERCA2A to Na + -Ca 2+ exchanger ratio [62].…”
Section: Cardiac Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports even suggest that exercise training can reduce the development of �brosis in established pathologic hypertrophy [61]. However, a very recent paper has shown that high levels of wheel running velocity in SHR rats can induce a pro�brotic phenotype and is positively correlated with LV mRNA of TGF-1, collagen III, and biglycan, whereas wheel running velocity was negatively correlated with SERCA2A to Na + -Ca 2+ exchanger ratio [62].…”
Section: Cardiac Remodelingmentioning
confidence: 99%
“…While extreme levels of acute and chronic exercise may be deleterious to the heart by increasing apoptosis, �brosis, and ischemic dysfunction [62,113,114], moderate levels of exercise seem protective from cardiac damage. ese animal studies support the American College of Sports Medicine recommendation for encouragement of exercise on most, if not all, days of the week, at moderate intensities, by accumulating 30 minutes or greater of endurance-style physical activity [7].…”
Section: -Adrenergic Responsivenessmentioning
confidence: 99%
“…Protein was extracted as described before (25). The lysis buffer contained (mmol/l): Tris-HCl (pH 7.5) 20, NaCl 150, EGTA 1, EDTA 2, Triton (1 % v/v), sodium pyrophosphate (2.5), β-glycerophosphate 1, Na 3 VO 4 1, leupeptin (1 µg/ml) (Cell Signalling Technology, Leiden, Netherland).…”
Section: Western Blotsmentioning
confidence: 99%
“…Tissue samples were prepared to analyse the steady-state mRNA levels of proteins of interest according to the previously described method (25). Briefly, total RNA was isolated from the left ventricles using peqGoldTriFast (peqlab, Biotechnology GmbH, Erlangen, Germany) according to the manufacturer's protocol.…”
Section: Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation